Analisis Peramalan Pemakaian Raw Material Round Bar Carbon Dengan Metode Single Moving Average (Studi Kasus PT Pindo Deli Pulp And Paper Mills – 2 Departemen Workshop) - Wawan Setiawan; Vita Efelina (Widya Teknik, 2021)
PT. Pindo Deli Pulp and Paper Mills 2 is a company engaged in the production of paper and tissue. This company consists of several departments. One of them is the workshop department. The department's material order system uses the SAP application, when the material is used, each input will reduce the amount of the initial material until the material approaches the least amount, the SAP application will automatically order the material to the supplier. however, this method is considered less effective, because for the use of the material itself, it is almost different from one another, which results in ordering materials at different times, once ordering the shipping cost also costs money. The number of orders always uses the initial order amount, as a result of which rarely used materials take up a lot of space. The approach that can be taken is the Forecasting method, namely Single Moving Average. This method produces material forecasting, D16: 2 kg, D20: 15.65 kg, D25: 61.55 kg, D30: 69.77 kg, D35: 101.04 kg, D40: 141.63 kg, D45: 16.60 kg, D50: 122.86 kg, D60: 63.73 kg, D65: 551.11 kg, D70: 258.62 kg, D75: 279.03 kg, D80: 317.68 kg, D90: 302.23 kg, D100: 596.97 kg